Peran iklim keselamatan terhadap perilaku aman karyawan - Yeni Ariska Wulandari; Djudiyah Djudiyah (Cognicia, 2024)
Safety behavior describes the actions of employees to protect themselves with the aim of avoiding hazards in the workplace. A positive safety climate indicates that the organization values a job and helps the health and well-being of workers. A supportive workplace safety climate will make employees feel safe at work. The purpose of this study is to determine the role of work safety climate on the safe behavior of employees in a company. This study uses a quantitative approach to study the relationship between two variables. Respondents in this study amounted to 150 employees of the mining company's production department which was taken using incident sampling techniques. The instruments in this study used the Nordic Safety Climate Questionnaire (NOSACQ 50) and safety behavior scale. The data analysis method used is simple regression analysis with the help of SPSS program version 25. The results showed that the safety climate had a significant effect on employee safe behavior (F = 47,093 with p = 0,000).